Effect of physical and technical training on the share of individual and collective tactical actions, in a official game of handball, at the juniors two (Jun. II) - Cicma, I. T.; Mereuta, C. (Science, Movement & Health, 2012)
The purpose of this paper is to present and demonstrate effects of an physical and technical optimal training, scientific and rigorously conducted on the share of the individual tactical actions and collective tactical combinations, in an official handball game. Methods. To verify the hypothesis and to achieve the purpose of this paper, there were used: specialty literature study method, the observation method, the experimental method, the game protocols elaboration and a individual observation records method, statistical-mathematical method, graphical method and data interpretation method. Results. We notice that, at the first game, without a special physical and technical training, the total share of a individual and collective tactical actions, was 55,33% percents, and in the second game, the total share of individual and collective tactic actions was 70% percents, progress being 14,67% percents. Conclusions. At the end, after studying game protocols and an individual observation records, we can say that the hypothesis was confirmed and the purpose has been reached. So we can conclude that through a physical and technical optimal training rigorous and scientific conducted, we can reach a positive effect on share of individual and collective actions, in an official game.